1982
DOI: 10.1203/00006450-198212000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cost of Growth in Very Low-Birth-Weight Infants

Abstract: Summaryied. The characteristics of each child are given in Table 1. NoneForty-eight measurements of energy expenditure were performed in 15 very low-birth-weight infants during the first 6 wk of life. Their mean birth weight and gestation age was 1223 g and 31 wk respectively. Their mean weight gain was 11.2 g/kg*d (range: -6.6 to +15.9 g/kg d.). The mean energy expenditure increased from 170 kJ/kg-d (wk 1) to 252 kJ/kg*d (wk 6). There was a significant relationship between weight gain and energy expenditure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 13 publications
3
34
0
1
Order By: Relevance
“…Gudinchet et al (4) measured vO, every 5 min for 24 h in three infants; the coefficients of variation were 3.5 to 6.6%. They concluded that nleasurements as brief as 1.5 h would be adequate to predict 24-h VOz.…”
Section: Resultsmentioning
confidence: 99%
“…Gudinchet et al (4) measured vO, every 5 min for 24 h in three infants; the coefficients of variation were 3.5 to 6.6%. They concluded that nleasurements as brief as 1.5 h would be adequate to predict 24-h VOz.…”
Section: Resultsmentioning
confidence: 99%
“…A previously described, open circuit indirect calorimeter was used to measure energy expenditure (5). Briefly the calorimeter consists of an airtight perspex box, containing the whole infant, placed inside the incubator.…”
Section: Methodsmentioning
confidence: 99%
“…However, measurements of energy expenditure in premature babies have been generally of short duration (5,(7)(8)(9), i.e. approximately 1-3 h. Therefore the extent to which these limited periods of measurement can be extrapolated to 24 h is still uncertain.…”
mentioning
confidence: 99%
“…Thus, in normal conditions, lipids deposited in adipose tissue are mainly of dietary origin. (4) The energy expended synthesising new tissue components arises in part from fat oxidation (Gudinchet et al, 1982). (5) There is an oxidation of fat related to physical activity (Bielinski et al, 1985) particularly in exercise of long duration and moderate intensity as is encountered in young children.…”
Section: Introductionmentioning
confidence: 99%